DYSMENORRHEA MANAGEMENT BY NON-MEDICAL FACULTIES STUDENTS OF UNIVERSITAS MUHAMMADIYAH SURAKARTA IN 2019 - HARLIANTI, MARISKA SRI; WIDIASTUTI, RATIH DWI (International Journal of Applied Pharmaceutics, 2021)
Objective: The aim of this study was to investigate the dysmenorrhea management by non-medical Faculties Students of Universitas Muhammadiyah Surakarta through self-medication. Methods: An observational study with cross-sectional design was conducted across 394 respondents at non-medical Faculties of Universitas Muhammadiyah Surakarta. Respondents were selected by purposive sampling method. Data were obtained using questionnaire that filled out by respondents. Results: Among the 394 respondents, 100% managed dysmenorrhea by non-pharmacological treatment (88.78%, 53.83%, and 42.35% were sleeping and taking a rest, eating nutritrious food, and compressing with warm water), whereas 160 (40.82%) respondents managed dysmenorrhea by taking medicines (70.62%, 16.88%, 11.25% and 1.25% were unidentified, over the counter, mandatory drug pharmacy [Obat Wajib Apotek], and prescription only medicine). Conclusion: Dysmenorrhea management among non-medical Faculties Students of Universitas Muhammadiyah frequently appropriate. The role of pharmacists in providing information about medicine used by community was very important because many respondents do not know the names or brands.